2018
DOI: 10.11005/jbm.2018.25.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump Inhibitor Use and Fracture Risk: An Updated Systematic Review and Meta-analysis

Abstract: BackgroundThis study's objective was to evaluate the association between proton-pump inhibitor (PPI) use and bone fracture incidence and bone mineral density (BMD) by meta-analyzing the estimates reported by epidemiological and cohort studies.MethodsData were acquired from studies identified after a literature search in electronic databases. Odds ratios (ORs), hazard ratios (HRs), and risk ratios (RRs) between PPI use and bone fracture incidence were pooled under the random effects model, and meta-analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 63 publications
2
46
0
2
Order By: Relevance
“…Such a possibility can never be excluded no matter how large the sample size of the trial. It is reassuring, however, that the HRs and ORs reported in this trial are lower than the lower end of the 95% CI of the observational data for pneumonia, 23 fracture, 26 cardiovascular disease, 27 chronic renal disease, 16 dementia, 17 and all-cause mortality. 18 Some data suggest adverse events associated with PPI therapy are not seen until after 5 years of therapy 36 and this trial had a mean follow-up of 3 years and a maximum follow-up of 5 years, which was achieved in only a small proportion of patients.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Such a possibility can never be excluded no matter how large the sample size of the trial. It is reassuring, however, that the HRs and ORs reported in this trial are lower than the lower end of the 95% CI of the observational data for pneumonia, 23 fracture, 26 cardiovascular disease, 27 chronic renal disease, 16 dementia, 17 and all-cause mortality. 18 Some data suggest adverse events associated with PPI therapy are not seen until after 5 years of therapy 36 and this trial had a mean follow-up of 3 years and a maximum follow-up of 5 years, which was achieved in only a small proportion of patients.…”
Section: Discussionmentioning
confidence: 59%
“…It is reassuring that there was no evidence for harm for most of these events other than an excess of enteric infections. This is in contrast to systematic reviews of observational studies that report the association of PPI therapy with harms such as pneumonia, 25 fracture, 26 and cerebrovascular events. 27 Biologically plausible mechanisms have been advanced to suggest these associations are causal, such as a PPI causing a change in the upper gastrointestinal tract microbiome, leading to pneumonia if aspirated 28 ; inhibition of calcium absorption leading to increased risk of fracture 29 ; and cardiovascular events may relate to PPIs reducing the activity of nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Clinicians, however, should remain vigilant for other exposures that may further predispose an already at‐risk cohort to fracture. For instance, proton pump inhibitors (PPI) have been linked to fractures and in Australia their use has increased by greater than 1000% from 1995 to 2006 . Fusaro et al found in a large study of 27 097 haemodialysis patients that almost half were on a PPI regimen and their use was associated with significantly higher rates of bone and hip fractures .…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published meta-analysis [ 313 ] which included 33 studies ( n = 2,714,502), subjects taking PPIs demonstrated a significantly increased overall fracture incidence (22.04% vs. 15.57% in controls) with pooling OR of 1.28 (95% CI 1.22–1.35); fracture risk raised with duration of PPI use (OR 1.29 in short users and 1.62 in long users), but no effect on BMD was found. Similar results were obtained in another meta-analysis [ 289 ]: PPI users, compared to non-users, had an increased risk of developing spine fracture (HR 1.49; 95% CI 1.31–1.68), hip fracture (HR 1.22; 95% CI 1.15–1.31), any-site fracture (HR 1.30; 95% CI 1.16–1.45) and OP (HR 1.23; 95% CI 1.06–1.42), but there was no correlation with BMD loss neither in the spine, nor in the hip.…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%